Pengaruh Formulasi Cendawan Entomopatogen Metharizium anisopliae(Metchnikoff) Sorokin dan Beauveria bassiana(Bals.-Criv.) Vuill terhadap Pertumbuhan dan Daya Tahan Hama Penyakit pada Bibit Kelapa Sawit (Pre nursery) - Gunawan, Juan Felix; Rahayuwati, Sat; Pratomo, Bayu; Afrianti, Suratni (Agroprimatech, 2024)
Entomopathogenic fungi are fungi that can cause death to insect pests. Some reports state that entomopathogenic fungi are endophytic or can grow in plant tissue and are positive for plant growth and produce phenol substances that insects do not like. The study aims to determine whether the formulation of entomopathogenic fungi Metharizium anisopliae (Metchnikoff) Sorokin and Beauveria bassiana (Bals.-Criv.) Vuill given to pre-nursery oil palm seedlings can help increase growth and resistance to pests and plant diseases. The study used factorial RAK with 3 replications and 2 factors, namely M. anisopliae fungus (M) with 4 levels: M0 = 0 g (control), M1 = 5g, M2 = 10g, and M3 = 40g, and B. bassiana fungus (B) with 4 levels namely: B0 = 0g (control), B1 = 5g, B2 = 10g, and B3 = 40g. The research resultsshowed that sprouts could grow into seedlings well, with an average third leaves appearing at week 12 after planting. The results of ANOVA analysis showed that the treatment factor of M. anisopliae and B. bassiana fungus gave an effect that was not significantly different on the parameters of the number of leaves, plant height, stem diameter, leaf length, number of leaf spots, leaf spot area, number of insect bites, insect bite area, plant length, crown wet weight, crown dry weight, root wet weight, root dry weight and root crown ratio. In other words, adding various doses of mixed formulation of M. anisopliae and B. bassiana did not provide a response to trigger plant growth and prevent the undesirable effects of insects. There are suggested that the two fungi are already in the oil palm seedling tissue as endophytes but until the 12th week, they have not shown any effect as a growth promotor or preventive effect the seddling tissue not liked by insects.